Generation Y on the e-commerce market: Comparison between Polish and South Korean young consumers behaviour - Aleksandra Korzeniowska (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2015)
This article investigates the problem of Polish and South Korean Millennials' consumer behaviour on the e-commerce market. There were arguments about whether Generation Y members as Digital Natives are rather a coherent or diversified cohort of consumers. They were raised in the culturally diversified world, but the trend of globalization and the use of the Internet may influence their consumer behaviour in a similar way. The aim of this paper is to reveal particular patterns crucial to understanding their way of making an online purchase. An online survey was conducted among Polish and South Korean respondents from Generation Y in order to investigate this issue. Besides being the representatives of culturally distant cultures, the two groups from the research sample revealed mostly convergent preferences and attitudes towards making an online purchase. Also, Polish and South Korean respondents revealed different attitudes online and offline, when compared to the cohort general analysis. In terms of making an online purchase via their mobile phones, Poles and Koreans remained coherent outside their national group and diversified inside their national group in terms of e-commerce but patterns slightly differed. Since this research was limited by too general e-commerce context, the aspect of making m-purchase should be investigated in the future.
Keywords: M30; M31; M39; M00; M16; M10; M19; M37; 650; e-Commerce; Generation Y; Poland; South Korea